2013
DOI: 10.5812/hepatmon.10106
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of Serum Apoptotic Cytokeratin 18 Neoepitope M30 (CK-18 M30) and Matrix Metalloproteinase 2 (MMP-2) Levels in Chronic Hepatitis B Patients with Cirrhosis

Abstract: BackgroundSerum apoptotic cytokeratine 18 neoepitope M30 (CK-18 M30) and matrix metalloproteinase 2 (MMP-2) have been popular markers for detecting liver fibrosis in recent years. CK-18 is a major intermediate filament protein in liver cells and one of the most prominent substrates of caspases during hepatocyte apoptosis. MMP-2 plays an important role in tissue remodeling and repairing processes during physiological and pathological states.ObjectivesThe objective of this study was to investigate the significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 31 publications
(40 reference statements)
3
27
0
Order By: Relevance
“…Our data are also in agreement with several observations by several authors who found increasing MMP-2 levels in chronic HCV patients where the most significant elevations were detected in those developing cirrhosis and HCC (27)(28)(29) .…”
Section: Discussionsupporting
confidence: 83%
“…Our data are also in agreement with several observations by several authors who found increasing MMP-2 levels in chronic HCV patients where the most significant elevations were detected in those developing cirrhosis and HCC (27)(28)(29) .…”
Section: Discussionsupporting
confidence: 83%
“…53,54 Thus, MMP-2-deficient mice show enhanced fibrosis after CCL 4 treatment and MMP-2 could be therefore critical for inhibiting type I collagen synthesis by activated HSCs, which strongly express this MMP. 55,56 MMP-9 and MMP-2 are elevated in serum and livers of patients with chronic hepatitis type B and C. [57][58][59] Elevated expression of MMPs in the mentioned fibrotic conditions was shown both in liver parenchyma 60 and portal macrophages. 57,61 Especially, MMP-9 seems to be involved in ongoing liver inflammation, 62 and its level drops after antiviral treatment.…”
Section: Metalloproteinases In the Development Of Liver Fibrosismentioning
confidence: 99%
“…The susceptibility to apoptotic cell death may depend on the HBV genotype, as well (22). Not only apoptotic cell death, but also autophagic cell death, may be good predictors for defining the level of liver injury at the beginning of treatment and during the follow-up period (23). …”
Section: Discussionmentioning
confidence: 99%